2014
DOI: 10.1063/1.4898632
|View full text |Cite
|
Sign up to set email alerts
|

Advances in three-dimensional rapid prototyping of microfluidic devices for biological applications

Abstract: The capability of 3D printing technologies for direct production of complex 3D structures in a single step has recently attracted an ever increasing interest within the field of microfluidics. Recently, ultrafast lasers have also allowed developing new methods for production of internal microfluidic channels within the bulk of glass and polymer materials by direct internal 3D laser writing. This review critically summarizes the latest advances in the production of microfluidic 3D structures by using 3D printin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 53 publications
0
101
0
Order By: Relevance
“…181 Instrumentation should ideally be also reconfigurable so that it can easily accommodate the integrated modular platform. 134,135,173 Future precision medicine will heavily depend on the ability to perform frequent liquid biopsies, and in general, on profiling various nucleic acids in serum and other physiological samples for screening, diagnostic, and prognostic applications in cancer and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…181 Instrumentation should ideally be also reconfigurable so that it can easily accommodate the integrated modular platform. 134,135,173 Future precision medicine will heavily depend on the ability to perform frequent liquid biopsies, and in general, on profiling various nucleic acids in serum and other physiological samples for screening, diagnostic, and prognostic applications in cancer and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…3D-printed templates also allow for accelerated testing and modification of device designs; modifications can be added to the template file and printed out immediately (Gross et al 2014;O'Neill et al 2014). MacDonald, et al (2002) have demonstrated a method to create microfluidic devices in PDMS using solid object printing.…”
Section: Introductionmentioning
confidence: 99%
“…The overall mechanism of these forces in 2D is straightforward. Alternatively, fabrication of 3-D microfluidic devices has been realized with 3-D printing technologies and direct internal 3-D laser writing methods, which was critically reviewed by O'Neill et al; 23 however, it is difficult to employ these 3-D fabrication technologies to embed electrodes in the microfluidic devices, that means, the electrokinetic forces are difficult to be employed to manipulate the particles in 3 dimensions.…”
Section: Introductionmentioning
confidence: 99%